THEORETICAL FUNDAMENTALS OF ENTERPRISE ECONOMIC POWER (Academicia Globe: Inderscience Research, 2022)
The article describes the concepts of potential, economic potential of the enterprise, scientific approaches, definitions, views, concepts of foreign and domestic scientists on their evaluation.